Faktor-Faktor Yang Mempengaruhi Perataan Laba Pada Perusahaan Manufaktur - Dwiputri, Nafisa Azzahra; Murni, Yetty; Fujianti, Lailah (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aims to determine the effect of Profitability, Firm Size, Audit Quality and Financial Leverage on Income Smoothing. This research method using quantitative descriptive method. The data used is secondary data with population using Consumer Goods Industry Sector Manufacturing Companies listed on Indonesia Stock Exchange for the period 2016-2020. The Sample was determined using purposive sampling and obtained 13 company samples. The analytical technique used in this research is logistic regression analysis and processed using SPSS ver25. The results showed that financial leverage has a significant negative effect on the actions of income smoothing, while profitability, firm size and audit quality has no effect on income smoothing with an R square value of 17,8%.